Selection of Design Parameters to Reduce the Zero-Sequence Circulating Current Flow in Parallel Operation of DC Linked Multiple Shunt APF Units. (8th December 2013) - Khadem, Shafiuzzaman K.; Basu, Malabika; Conlon, Michael F.
Abstract : Capacity enhancement and operational flexibility are two of the important limitations of the centralized shunt APF (APF sh ) unit. These limitations can be conquered by the operation of multiple APF units in parallel and connected back to back by a common DC link capacitor. In that case, a circulating current (CC) flows within the APF sh units. This CC flow becomes out of control when the APF sh units operate in hysteresis based current controlled mode. One of the difficulties of this CC flow control or reduction is the variable switching frequency of the APF sh units. In this paper, the model for CC flow is derived by the switching dynamics study of the APF sh units. It is found that the selection of design parameters plays an important role in the amount of CC flow. Detailed simulation, analysis, and real-time performance show how the selection of design parameters affects the CC flow and the reduction of CC flow can also be achieved at an acceptable level by the proper selection of design parameters.